1989
DOI: 10.1152/physiologyonline.1989.4.6.219
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Autoregulation of Systemic Blood Flow and Cardiac Output

Abstract: The contribution of local autoregulatory mechanisms to the overall control of the systemic circulation has been analyzed using theoretical and experimental approaches. Mechanisms that regulate regional vascular resistance and contribute importantly to the overall moment-to-moment regulation of cardiac output and total peripheral resistance are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Mathematical models of the cardiovascular system that include regulatory effects have been in common use for several decades . These models generally consist of a set of coupled subsystems.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical models of the cardiovascular system that include regulatory effects have been in common use for several decades . These models generally consist of a set of coupled subsystems.…”
Section: Introductionmentioning
confidence: 99%
“…It plays an important role in ion homeostasis and regulation of cerebral microvascular resistance. Therefore, we aimed to investigate the effects of both AV and AV V1 receptor specific antagonist on CVS and morphological changes in vessels (3,6,8,9,17,23).…”
Section: █ Discussionmentioning
confidence: 99%
“…Also, the results of baroreceptor studies in humans suggest caution in this respect because reflex sensitivity may either increase or decrease (Conway et al, 1983) in REM sleep. At this point, it appears likely that circulation in different species is affected by similar central influences in REM sleep, although the eventual pattern of change in cardiovascular variables also depends on species-specific differences in the operation of feedback loops (Gilmore and Tomomatsu, 1984) and peripheral autoregulation (Cowley et al, 1989).…”
Section: Rem Sleepmentioning
confidence: 99%
“…The importance of such an interaction is also shown by studies in anesthetised (Gebber et al, 1990) and awake (Ninomiya et al, 1990) cats, which demonstrated that the central generator underlying the rhythmicity of synchronised cardiac sympathetic nerve activity is subject to reflex modulation by baroreceptor inputs. In addition, the patterns of change in cardiovascular variables also depend on species-specific differences in the operation of feedback loops (Gilmore and Tomomatsu, 1984;Sindrup et al, 1992) and auto-regulation (Baccelli et al, 1974;Cowley et al, 1989). However, the prevalence of an unstable central autonomic command plays a substantial role in the variability of circulatory events in REM sleep (see Parmeggiani, 1994;Silvani and Lenzi, 2005).…”
Section: Rem Sleepmentioning
confidence: 99%